Trace Metals in Nectar of Important Urban Pollinator Forage Plants: A Direct Exposure Risk to Pollinators and Nectar‐Feeding Animals in Cities - Sarah B. Scott; Mary M. Gardiner (Ecology and Evolution)
ABSTRACT Pollinators are exposed to metals while foraging in the landscape and accumulate detectable concentrations of trace metals within their bodies, although major exposure routes remain unclear. As nectar is the main source of food for pollinators, we analyzed trace metal content within floral rewards to identify if nectar contained detectable metals and may serve as an oral exposure route. Nectar from flowering plant species growing within vacant lots in the city of Cleveland, OH, USA was extracted using a centrifuge and tested for the metals arsenic, cadmium, chromium, and lead using ICP‐MS. We collected volunteer flower species that are common pollinator forage plants. Nectar metal content varied by plant and metal species, but not by location. Nectar arsenic concentrations ranged from 0 to 8.44 μg/L, cadmium from 0 to 32.99 μg/L, chromium from 0 to 45.69 μg/L, and lead from 0 to 135.31 μg/L. The presence of these soil contaminants in nectar indicates that the uptake and concentration of metals within nectar resources is likely a major route of metal exposure for pollinators and nectar‐feeding animals.